I have a problem that states: Write each english sentence in symbolic form using the following predicates: m = Melissa p = Pizza S(x) = ' x is a student ' L(x, y) = ' x likes y ' E(x, y) = ' x eats y ' Take A as the universal quantifier in this problem and M as the existential quantifier since E is already being used. I know that when: a) All students eat pizza. I get this Ax (S(x) -> E(x, p) ) but when b) Only students eat pizza. I get confused when the word only is used. Is there a better way to view this sentence that would make it more obvious what the answer would be?